2012
DOI: 10.1016/j.molcel.2012.01.016
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-Binding Protein HuD Controls Insulin Translation

Abstract: Although expression of the mammalian RNA-binding protein HuD was considered to be restricted to neurons, we report that HuD is present in pancreatic β cells, where its levels are controlled by the insulin receptor pathway. We found that HuD associated with a 22-nucleotide segment of the 5'-untranslated region (UTR) of preproinsulin (Ins2) mRNA. Modulating HuD abundance did not alter Ins2 mRNA levels, but HuD overexpression decreased Ins2 mRNA translation and insulin production, and conversely, HuD silencing en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 22 publications
4
118
0
Order By: Relevance
“…Elavl4 acts as a master regulator of neurogenesis, regulating neuronal survival, function, and plasticity (34, 36 -38). In pancreatic beta cells Elavl4 has been shown to regulate insulin translation (39), autophagy (40), and lipid synthesis (41). Here we show that Elavl4 also regulates cell survival in beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…Elavl4 acts as a master regulator of neurogenesis, regulating neuronal survival, function, and plasticity (34, 36 -38). In pancreatic beta cells Elavl4 has been shown to regulate insulin translation (39), autophagy (40), and lipid synthesis (41). Here we show that Elavl4 also regulates cell survival in beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 However, we found that HuD is also present in pancreatic β-cells, where its levels are controlled by the IR pathway. 52 In β-cells, HuD binding to the Ins2 5'-UTR repressed Ins2 mRNA translation and decreased insulin production. Accordingly, HuD-null mice expressed higher levels of insulin in β-cells, while HuD-transgenic mice expressed lower insulin levels in β-cells.…”
Section: Lipid Homeostasismentioning
confidence: 95%
“…52 Similar to two other Hu/ELAV family members (HuB and HuC), HuD was believed to be expressed specifically in neurons. 53,54 However, we found that HuD is also present in pancreatic β-cells, where its levels are controlled by the IR pathway.…”
Section: Lipid Homeostasismentioning
confidence: 97%
“…Recent studies showed that HuD is regulated by the microRNA miR-375 which suppressed neuritis outgrowth [49]. In pancreatic β cells HuD was also found to bind the 5'UTR of preproinsulin mRNA and negatively regulate mRNA translation [50]. These findings suggest that HuD is expressed in other tissues than neuronal tissues and might have important regulatory functions yet to be investigated.…”
Section: Hudmentioning
confidence: 93%
“…This RBP was initially described as neuronal specific [13]; however recent studies have shown HuD to be expressed in other cells such as pancreatic β cells [49,50]. HuD is essential for neuronal development, identity, and differentiation through stabilization of mRNAs encoding proteins involved in these processes such as growth associated protein 43 (GAP-43), p21, acetylcholinesterase (AchE), and other targets [51][52][53][54].…”
Section: Hudmentioning
confidence: 99%